Betacyanins from red pitahaya (Hylocereus polyrhizus) exhibit antiviral response against influenza A virus - Lim, Chie Min; Lal, Sunil Kumar; Isa, Nurulfiza Mat; Omar, Abdul Rahman; Choo, Wee Sim (Elsevier, 2024)
Seasonal influenza affects millions of lives worldwide, with the influenza A virus (IAV) responsible for pandemics and annual epidemics, causing the most severe illnesses resulting in patient hospitalizations or death. With IAV threatening the next global influenza pandemic, it is a race against time to search for antiviral drugs. Betacyanins are unique nitrogen-containing and water-soluble reddish-violet pigments that have been reported to possess antiviral properties against the dengue virus. This study aimed to examine the antiviral effect of betacyanins from red pitahaya (Hylocereus polyrhizus) on IAV-infected lung epithelial A549 cells. HPLC and LC-MS analysis of extracted betacyanin showed four betacyanins in the betacyanin fraction: phyllocactin, hylocerenin, betanin, and isobetanin. Cytotoxicity assay showed that betacyanin fractions were not cytotoxic to A549 cells at concentrations below 100 μg/mL. Betacyanin fraction concentrations of 12.5, 25.0, and 50.0 μg/mL prevented the formation of viral cytopathic effect and reduced virus titer in IAV-infected cells up to 72 h. A downregulation of protein and mRNA nucleoprotein expression levels was observed after treatment with 25.0 and 50.0 μg/mL of betacyanin fraction after 24 h, thereby providing evidence for the antiviral activity of betacyanin from red pitahaya against IAV in vitro.